Theoretical and experimental investigation of the effect of acetic and formic acids as capping agents on morphology of KTiOPO4 nanoparticles - Elaheh Gharibshahian; Fatemeh Shokri; Mohamad Saeed Yazdani; Majid Jafar Tafreshi (Nanochemistry Research)
KTiOPO4(KTP)nanoparticles were synthesized using acetic and formic acids as capping agents by the co-precipitation method for the first time. X-Ray diffraction (XRD) and Fourier Transform Infrared (FT-IR) analyses confirmed the formation of the KTP structure with an orthorhombic phase. The effect of capping agents on the structural and morphological properties of obtained KTP nanoparticles was studied. The Biggest grain size(66nm) and lattice strain (0.0056) were obtained using acetic acid and formic acid, respectively. Using acetic and formic acids resulted in the rotation of the crystal lattice and an increase in the grain size. Acetic acid prevented the agglomeration of synthesized KTP nanoparticles after calcination, and resulted in uniform size distribution. Theoretical computations and FE-SEM analysis were used for morphological studies. FE-SEM analysis shows acetic acid results in the spherical form of nanoparticles, and using formic acid leads some nanoparticles ‘morphology to oriented growth. Theoretical computations confirmed these results. The structural energy of the most stable KTP nanostructures obtained using formic acid as a capping agent was ∆E=-202∙6518584 kj⁄mol and ∆E=-196∙613208 kj⁄mol. The first formation energy belongs to the oriented template of the nano-particles.